2020
DOI: 10.1103/physrevb.102.054424
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent spin polarization of Heusler Co2MnSi from the disordered local-moment approach: Effects of atomic disordering and nonstoichiometry

Abstract: Half-metallic ferromagnets have been widely investigated by first-principles density-functional theory (DFT) calculations, but extending such studies to investigate spin-polarization at finite temperatures is still challenging due to the difficulty of incorporating temperature effects appropriately. We present DFT calculations, based on a Green's function formulation, which include thermal effects via the disordered local-moment method to address this issue. The calculations are carried out for Heusler Co 2 Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…As shown in Fig. 1(b), increasing the temperature enhances spin fluctuations in d-electron states, as suggested in previous studies [16][17][18][19]. We find that such spin fluctuations propagate from d-to s-electron states through the sd exchange interaction.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…As shown in Fig. 1(b), increasing the temperature enhances spin fluctuations in d-electron states, as suggested in previous studies [16][17][18][19]. We find that such spin fluctuations propagate from d-to s-electron states through the sd exchange interaction.…”
supporting
confidence: 87%
“…A clue to explain this phenomenon is conduction sp-electron states in ferromagnets; several experiments [7,10] have shown that sp-electron states with smaller effective mass than d-electron states provide dominant contributions to transport properties of MTJs. However, most previous theories [12][13][14][15][16][17][18][19] have focused only on delectron states and dd exchange interaction between d electrons on neighboring sites. This is because d-electron states have large density of states around the Fermi level and play the main role for static magnetic properties in bulk ferromagnets at finite temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, since the FM layer in this study is composed of one of the Co-based Heusler alloys, we should consider the influence of the structural disorder in the Co-based Heusler alloy on the temperature-dependent P inj=det in FM/SC LSV devices. Actually, recent theoretical studies have already discussed the correlation between the atomic-level disorder including nonstoichiometries in Co-based Heusler alloys and the bulk P with increasing T. 52,53 For high-performance FM-SC hybrid devices above room temperature, it will be essential to discuss the influence of the atomic disorder near the interfaces on the temperature-dependent P inj=det in future.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…Here, S is the spin operator. The value of this quantity at the Fermi level (E = E F ) is of particular interest when investigating magnetoresistive devices [30].…”
Section: Calculating the Integrated Density Spin And Orbital Momentsmentioning
confidence: 99%